A NOTE ON SOCIALLY ENGAGED ART CRITICISM - Rasmussen, Mikkel Bolt (The Nordic Journal of Aesthetics, 2017)
This article is a discussion of Grant Kester’s notion of socially-engaged art criticism via a retrospective mapping of the four most important 1990s artistic practices: relational art, institutional critique, tactical media and socially-engaged art. While both relational, or participatory, art and institutional critique seem to have run out of steam, and have fused more or less seamlessly with the institution of art, socially-engaged art still seems to hold critical potential by making use of the relative autonomy of art beyond the narrow confines of the art institution. The journal Field, founded and edited by Kester, is an attempt to develop a new art criticism that is able to account for this kind of practice. The turn to ethnography in order to analyse often open-ended community-based projects is relevant – and the